EMERGENCY STATE OF MANDIBLE FRACTURE MANAGEMENT IN COVID-19 PANDEMIC AREA: A CASE REPORT - Popovski, Vladimir; Benedetti, Alberto; Panchevski, Goran; Bajro, Abdulkerim; Stamatoski, Aleksandar (Journal of Morphological Sciences; Vol 3 No 3 (2020): JMS, 2020)
â€œComminutedâ€ mandibular fracture occurs when a high-energy impact on mandibular or different or multiple regions is applied, with disrupted lines of the lower jaw. Cartographic mapping of the maxillofacial complex should be carefully analyzed by a physician, because the diagnosis is difficult to be established due to facial edema masquerading the clinical features, and in most of the cases abnormal bite. We describe a case of extensively complex comminuted mandibular fracture in symphyseal and parasymphyseal  area treated with open reduction, internal fixation and reconstruction in a 20-year-old male patient. Reestablishing function, anatomy and aesthetics were the primary postsurgical goals regarding treatment modality. Immediate blood control was achieved and sound bone healing was confirmed in the second step surgery via extraoral surgery with anatomical landmarks.  Surgical technique regarding fracture repositioning avoiding neurovascular damage and minimal facial scaring resulted with satisfactory occlusion. A follow-up period of 3 months did not show any changes, disadvantages and differences regarding treatment. We have concluded and once again established that the existing and future surgical practice needs to undergo some changes according to proposed algorithms at the time of Covid19 infection. Keywords : mandible fracture; comminuted fracture; ORIF; craniofacial trauma